Radiogenic Isotopes in Geologic Processes - Rasskazov, Sergei V. (Springer Netherlands : Imprint: Springer, 2010)
This book presents a modern approach of radiogenic isotope methods for solutions on problems in theoretical and practical geology. New approaches on thermochronology are of particular interest. Results on age measurements for timing of the Earth’s formation, main stages in evolution of biota in the Phanerozoic, and the most important tectonic and magmatic events in the Late Mesozoic through the Cenozoic of Central and East Asia, the western margin of North America, and Northeastern Africa are discussed. Systematics of magmatic sources in terms of isotope geochemistry in continents and ocean-continent transition zones are covered. Formal mathematical considerations on radiogenic isotope geology that are presented in a simple way with numerical examples and tables that can be used for solutions of theoretical problems on the origin and evolution of the Earth as well as for correct selection of material in regional geochronological studies and dating of individual geological objects. Audience: This book is intended for scientists, researchers and professionals in geochemistry, geochronology and in Earth and environmental sciences. It is also of interest to students in radiogenic isotope courses.